Harnessing microbial science to accelerate the United Nations sustainable development goals. Issue 7 (10th July 2020) - Fagunwa, Omololu; Atinuke, Afolake
Abstract : Modernisation has thrown humanity and other forms of life on our planet into ditch of problems. Poverty, climate change, injustice, environmental degradation are few of the shared global problems. The United Nations SDGs are set as blueprint to achieve a better and more sustainable future for all. The SDGs are well structured to address the global challenges we face including poverty, inequalities, hunger, climate change, environmental degradation, peace and justice. The SDGs have been driven mainly by international donors and 'professional' international development organisations. The world is left with 10 years to achieve these ambitious goals and targets. Various reviews indicated that little has been achieve on overall, and the SDGs will not be reality if new strategy is not in place to bring inclusion. Microbiology, the scientific discipline of microbes, their effects and practical uses has insightful influence on our day to day living. We present how microbiology and microbiologists could increase the scorecard and accelerate these global goals. Microbiology contribution to peace, justice, gender equality, decent work and economic growth will be also highlighted among others. The pledge of Leave No One Behind will fast track progress and microbiology is better position to make this work.